EFEKTIFITAS PENERAPAN PROSEDUR TANGGAP DARURAT LPADA PT PUNINAR INFINITE RAYA DI BAIKPAPAN - Maslina , Maslina; Munahar, Munahar; Rahmahniar , Andi (IDENTIFIKASI, 2021)
Fires have detrimental effects, including: human casualties, lost or reduced job opportunities, and others. In Balikpapan, fires were recorded from the Regional Disaster Management Agency's recapitulation for the last 6 years, there were 417 cases of building fires. PT Puninar Infinite Raya Balikpapan is a company engaged in logistics, warehouse and trucking as well as custom clearance, which has activities that can trigger flashpoints that can cause fires during work. The type of research used is descriptive with a qualitative approach. This study was conducted to determine whether or not the implementation of emergency response procedures at PT Puninar Infinite Raya Balikpapan was appropriate. As a basis of reference in matching data at PT Puninar Infinite Raya, the author uses the SOP Emergency Response Plan (PIR-SOP-007/HSE) of PT Puninar Infinite Raya and the Minister of Public Works Regulation No. 26 of 2008, concerning Technical Requirements for Fire Protection Systems in Buildings and the Environment. as a reference to find evidence of discrepancies in the study, the authors will conduct interviews to find evidence of discrepancies and use the formulation of effectiveness. The test results from this study with an average value of the application rate of fire emergency response procedures of 90.5% which means that it is effective at PT Puninar Infinite Raya. Based on the level of conformity of Emergency Procedures and SOPs at 78%, Emergency Response Units at 83%, Egress Facilities at 82%, Gathering Places at 100%, Maintenance and Installation of APARs at 100% and Fire Alarms at 100%.